Characterization of White Matter Injury in a Rat Model of Chronic Cerebral Hypoperfusion. Issue 2 (February 2016) - Choi, Bo-Ryoung; Kim, Dong-Hee; Back, Dong Bin; Kang, Chung Hwan; Moon, Won-Jin; Han, Jung-Soo; Choi, Dong-Hee; Kwon, Kyoung Ja; Shin, Chan Young; Kim, Bo-Ram; Lee, Jongmin; Han, Seol-Heui; et al.
Abstract : Background and Purpose—: Chronic cerebral hypoperfusion can lead to ischemic white matter injury resulting in vascular dementia. To characterize white matter injury in vascular dementia, we investigated disintegration of diverse white matter components using a rat model of chronic cerebral hypoperfusion. Methods—: Chronic cerebral hypoperfusion was modeled in Wistar rats by permanent occlusion of the bilateral common carotid arteries. We performed cognitive behavioral tests, including the water maze task, odor discrimination task, and novel object test; histological investigation of neuroinflammation, oligodendrocytes, myelin basic protein, and nodal or paranodal proteins at the nodes of Ranvier; and serial diffusion tensor imaging. Cilostazol was administered to protect against white matter injury. Results—: Diverse cognitive impairments were induced by chronic cerebral hypoperfusion. Disintegration of white matter was characterized by neuroinflammation, loss of oligodendrocytes, attenuation of myelin density, structural derangement at the nodes of Ranvier, and disintegration of white matter tracts. Cilostazol protected against cognitive impairments and white matter disintegration. Conclusions—: White matter injury induced by chronic cerebral hypoperfusion can be characterized by disintegration of diverse white matter components. Cilostazol might be a therapeutic strategy against white matter disintegration in patients with vascular dementia. Abstract : Supplemental Digital Content is available in the text.